Analisis Karakter Religius Dalam Kitab Ta’liim Al-Muta’allim Karya Imam Al-Zarnuji Dan Implikasinya Terhadap Pendidikan Karakter (Kajian Ilmu Pendidikan Islam) - Salamudin, Ceceng; Alawiyah, Imaroh (STAI Al-Musaddadiyah Garut, 2023)
The moral crisis among students, exemplified by drug abuse, bullying, plagiarism, and sexual violence, necessitates ongoing research by Islamic education scholars into religious texts written by prominent scholars. These studies aim to reinforce the conceptual foundations that can be proposed as solutions to these moral issues. The book